2009
DOI: 10.1128/jvi.00168-09
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of the First and Next Generations of Human Immunodeficiency Virus (HIV) Fusion Inhibitors Exhibit a Highly Potent Synergistic Effect against Enfuvirtide- Sensitive and -Resistant HIV Type 1 Strains

Abstract: T20 (generic name, enfuvirtide; brand name, Fuzeon) is a first-generation human immunodeficiency virus (HIV) fusion inhibitor approved for salvage therapy of HIV-infected patients refractory to current antiretroviral drugs. However, its clinical use is limited because of rapid emergence of T20-resistant viruses in T20-treated patients. Therefore, T1249 and T1144 are being developed as the second-and third-generation HIV fusion inhibitors, respectively, with improved efficacy and drug resistance profiles. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 62 publications
1
43
0
1
Order By: Relevance
“…Our results showed that T-20-derived peptides seem less active compared with C34 derivatives with N-TRD. Recently, treatment with two or three fusion inhibitors was reported to have a potent and syn-ergistic antiviral activity on T-20-resistant variants (48,49). Together, these observations indicated that each inhibitor has a distinct inhibitory mechanism that may lead to the design of a combination therapy of fusion inhibitors in vivo.…”
Section: Table 3 Antiviral Activity Of Fusion Inhibitors To Sc34-and mentioning
confidence: 94%
“…Our results showed that T-20-derived peptides seem less active compared with C34 derivatives with N-TRD. Recently, treatment with two or three fusion inhibitors was reported to have a potent and syn-ergistic antiviral activity on T-20-resistant variants (48,49). Together, these observations indicated that each inhibitor has a distinct inhibitory mechanism that may lead to the design of a combination therapy of fusion inhibitors in vivo.…”
Section: Table 3 Antiviral Activity Of Fusion Inhibitors To Sc34-and mentioning
confidence: 94%
“…Based on our results, the combinational application of HIV-1 fusion inhibitors targeting different sites in NHR, such as CP32M and T20, which mainly target the C-terminal pocket region and the N-terminal GIV motif in the gp41 NHR domain, respectively, is expected to have a synergistic anti-HIV-1 effect, especially against the drug-resistant viral strains, since our previous studies demonstrated this effect when the first-and-next generation HIV fusion inhibitors were combined (31,33). Similarly, a longer peptide containing all the functional domains in CHR may be effective against viruses with mutations resistant to both CP32M and T20.…”
mentioning
confidence: 99%
“…For example, combination of enfuvirtide (T20), which binds to the N-terminal region of NHR (containing the GIV motif) but lacks the pocket-binding domain, with sifuvirtide or T1144 (both contain the pocket-binding domain) resulted in strong synergistic antiviral activity against a broad spectrum of HIV-1 strains, especially those resistant to T20 [92,93]. Based on this result, we designed a chimera peptide consisting of T20, a 35-mer linker and T1144, designed TLT35, which showed high potency against HIV-1 gp41-mediated cell-cell fusion and HIV-1 infection [94].…”
Section: Synergistic Combinations Of Multiple Hiv Entry Inhibitorsmentioning
confidence: 99%